Village Autonomy: The Main Road to Fulfill Right to Water - Ardhiwinda Kusumaputra; Indra Perwira; Ida Nurlinda (Faculty of Law, Hasanuddin University, 2018)
Water resources are common resources that affect the livelihood of many people. Its management should be oriented towards the rights fulfillment to water for the community. However, the management of water resources still shows inconsistency. This results in uncertainty in the rights fulfillment to water for the community. Therefore, a reform in water resources management is needed. Village autonomy can be the foundation for a more community-oriented water rights management, since it contains independence and community initiatives. This research aimed at finding a precise and clear concept in the management of water resources based on village autonomy. This research was conducted using normative juridical, with legislative and doctrinal approaches. The results show that the concept of village autonomy-based water resources management is carried out by accommodating the community's rights on water resources. It aims at providing guidance in the implementation of management that is not only oriented to exploitation, but also consider the aspects of conservation and control of water resources. This conception is expected to be implemented in village communities (not customary village communities) so as to be able to fulfill the rights to water to village communities justly and democratically.